Allusions and Reflections : Greek and Roman Mythology in Renaissance Europe. - Nivre, Elisabeth Wåghäll (Cambridge Scholars Publishing, 2015)
In June 2012, scholars from a number of disciplines and countries gathered in Stockholm to discuss the representation of ancient mythology in Renaissance Europe. This symposium was an opportunity for the participants to cross disciplinary borders and to problematize a well-researched field. The aim was to move beyond a view of mythology as mere propaganda in order to promote an understanding of ancient tales and fables as contemporary means to explain and comprehend the Early Modern world. W ...